2009
DOI: 10.1097/mbp.0b013e32833128d4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of passive leg raising on arterial wave reflection in healthy adults

Abstract: PLR decreases the amplitude and delays the onset of the reflected aortic pressure wave. This decreases wasted LV pressure energy and workload.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
1
9
2
Order By: Relevance
“…Previous studies on PLR in healthy subjects reported transient changes of cardiovascular dynamics by PLR, but failed to show significant lasting effects of PLR [4][5][6][7]. In contrast, the present study revealed significant sustained effects on cardiovascular parameters even at 10 min after the start of PLR.…”
Section: Effects Of Plr On Cardiovascular Parameters and Their Durationcontrasting
confidence: 93%
See 1 more Smart Citation
“…Previous studies on PLR in healthy subjects reported transient changes of cardiovascular dynamics by PLR, but failed to show significant lasting effects of PLR [4][5][6][7]. In contrast, the present study revealed significant sustained effects on cardiovascular parameters even at 10 min after the start of PLR.…”
Section: Effects Of Plr On Cardiovascular Parameters and Their Durationcontrasting
confidence: 93%
“…The aim of this procedure is to improve blood circulation by facilitating venous return from the lower limbs [1][2][3][4][5][6][7][8][9][10]. However, several studies have cast doubts on the efficacy and duration of the effects of PLR [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Tr was the same for both groups; in general increased arterial stiffness or a reduction in reflection site distance causes a decrease in Tr. Since Tr is related to ejection duration [59], arterial stiffness can change without a change in Tr. Indeed, if Tr is corrected for ejection duration then there is a decrease in this variable.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve studies were identified and examined to determine whether normalizing AIx to HR influences the interpretation of the findings (Table 1). Eight studies reported significantly improved between-group/condition differences using the AIx@75 versus the AIx alone [23][24][25][26][27][28][29] , two studies reported no significant differences using the AIx but a significant difference using AIx@75 30,31) , one study reported a decrease in significance using the AIx@75 32) and one study reported a change in the direction of the effect 33) . Given these findings, careful interpretation of the physiological significance of normalization to HR is warranted.…”
Section: Validity Of the Aix And Influence Of Normalization To Hrmentioning
confidence: 99%